Cytomegalovirus-associated transverse myelitis: a review of nine well-documented cases. Issue 1 (January 2015) - Arslan, Ferhat; Yilmaz, Mesut; Paksoy, Yahya; Karagöz, Ergenekon; Mert, Ali
Abstract: Cytomegalovirus-associated transverse myelitis is a rare disease. We found 12 cases in the medical literature, 8 of which met our criteria for being well documented. Our aim was to review this clinical entity using information from our own clinical experience as well as published cases.